Study on the Structural Plane Characteristics and Disaster-Induced Mechanism of the Yellow River Jingtai Stone Forest, Northwestern Loess Plateau, China - Lyu, Yan; Gu, Gang; Wang, Zuopeng; Leng, Yanqiu; Ma, Penghui; Peng, Jianbing (Frontiers in Earth Science, 2022)
The Yellow River Jingtai Stone Forest is situated in the northwestern margin of the Loess Plateau China, and it is not only one of the most precious and rare types of natural landforms in the Loess Plateau, but also a protected area of valuable geological relics and landscapes in Northwest China. Massive structural planes are developed in the stone forest. However, few studies have been done on the rock mass structural plane for the slope stability. Based on the detailed field investigation, this paper classifies structural planes and their combination types in the rock mass. On this basis, combined with physical, mechanical and hydraulic tests, disaster-inducing mechanism of the rock mass structural plane are classified and discussed. Results show the structural plane of the Jingtai Stone Forest can be divided into three types, including primary structural plane, tectonic structural plane and secondary plane. They not only combine with each other to cut the rock mass into different-shape blocks, but also jointly control the stability of the rock mass slope. The physical and mechanical tests and water sensitivity characteristics show that the conglomerate and muddy sandstone which are the main components of the Jingtai Stone Forest have strong tensile and shear strengths under natural situation, while their strengths are reduced under immersion infiltration, especially the muddy sandstone is more sensitive to water, and has a lower strength than the conglomerate. Finally, the failure mechanism of the Jingtai Stone Forest is mainly related to the combination of various structural planes, which can be divided into four failure patterns, that is, creeping slide-tension failure, gradual failure, slipping failure and dumping failure. The studied results will provide critical theoretical and technical support for the slope stability analysis, scenic geological heritage protection and disaster warning in this area.